Sistem Pendukung Keputusan Penerimaan Mahasiswa Baru dengan FAM (Studi Kasus : Politeknik Indramayu) - Widyawan; Munengsih Sari Bunga (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Polytechnic Indramayu is a new Polytechnic established by the District Government of Indramayu based on the Decree of the National Education Minister of Republik Indonesia Number 124/D/O/2008 and District Local Regulation of Indramayu No.5 of 2008. In accordance with its mission to prepare graduates who are competent in their field, the selection process is required to capture prospective students and to prepare their ability to compete in the global market. The selection process is conducted based on several criteria including the score of test entrance, highschool certificate, academic and non-academic achievement, age, and parental income for determining who will be accepted as a student. Issues to be resolved through this thesis is how to design a web-based decision support systems and sms using Fuzzy Associative Memory (FAM) to determine who will be accepted as a student at Polytechnic Indramayu by grouping data into two categories of new students, accepted or not accepted. SMS Gateway in this study only run the process of sending data information of students who are accepted as a new student. Test is conducted using 20 samples of student data. The number of 20 applicants can be processed by decision support systems that are made and the announcement of the results of entrance examinations and the results of new admissions can be done more quickly in about one week.